2014
DOI: 10.1177/0003489414542845
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Ethanol Ablation for Thyroglossal Duct Cyst

Abstract: Ethanol ablation is a feasible and convenient procedure without surgical scars and hospitalization for TGDC patients. Favorable outcomes can be achieved without significant complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 12 publications
(31 reference statements)
0
34
0
1
Order By: Relevance
“…We used ethanol as the ablative agent because it is both readily available and inexpensive. Ethanol is a very caustic agent, and is used as an effective sclerosant in many clinical scenarios [ 17-20 ]. Ethanol destroys cells via dehydration, protein denaturation, coagulation, necrosis, small vessel thrombosis, haemorrhagic infarction, and reactive fibrosis [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We used ethanol as the ablative agent because it is both readily available and inexpensive. Ethanol is a very caustic agent, and is used as an effective sclerosant in many clinical scenarios [ 17-20 ]. Ethanol destroys cells via dehydration, protein denaturation, coagulation, necrosis, small vessel thrombosis, haemorrhagic infarction, and reactive fibrosis [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ethanol is a very caustic agent, and is used as an effective sclerosant in many clinical scenarios [ 17-20 ]. Ethanol destroys cells via dehydration, protein denaturation, coagulation, necrosis, small vessel thrombosis, haemorrhagic infarction, and reactive fibrosis [ 17 ]. After the initial inflammatory insult, damaged cells are replaced with connective tissue preventing regrowth [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, ever more radical resection of the tongue base risks fistula formation and injury to hypoglossal nerve branches. There are a few reports describing the use of injected sclerosing agents 32,33 or intraluminal electrodessication 34 to control recurrent disease. These have not been replicated in large series with long-term follow-up.…”
Section: The Suprahyoid Compartmentmentioning
confidence: 99%
“…The former imaging was performed with 1 of 3 US systems: an iU22 ultrasound machine (Philips Healthcare, Best, the Netherlands), Acuson S2000 (Siemens, Erlangen, Germany), or an EUB-7500 HV (Hitachi Medical Systems, Tokyo, Japan). All 3 were equipped with a high-frequency linear probe (5)(6)(7)(8)(9)(10)(11)(12)(13)(14). The index cyst volume was calculated as V ϭ abc / 6, where V is the volume, a is the largest diameter, and b and c are the other 2 perpendicular diameters.…”
Section: Preprocedural Assessmentmentioning
confidence: 99%
“…Therefore, minimally invasive treatment such as ultrasonography (US)-guided chemical ablation has been suggested as an alternative treatment for BCC. [2][3][4][5][6][7] Both chemical ablation with picibanil (OK-432) and ethanol ablation (EA) are widely used to treat cystic lesions of the neck and oral cavity, such as thyroid cyst, ranula, and lymphatic malformation, [8][9][10][11][12][13] but only a few studies have focused on the use of either treatment in BCCs. Since Fukumoto et al 2 initially used EA on 3 BCCs in 1994, several studies have reported success rates of roughly 60% in patients with BCC treated with OK-432.…”
mentioning
confidence: 99%